Miniplate fixation osteosynthesis of isolated mandibular symphyseal fracture without involvement of bilateral condyle in a helmet wearer - Shunmugavelu, Karthik; Subramaniam, Kumaravel (International Journal of Dental Research, 2016)
A peculiar case of vertical mandibular symphyseal fracture in a helmet wearer has been presented. Under general anesthesia, fracture site was exposed through intraoral mandibular labial vestibule incision. Open reduction and internal fixation was done with two four holed titanium miniplates and screws. Healing was uneventful. Complete recovery was found after 6 months.